DEVELOPING TASK-BASED SUPPLEMENTARY ENGLISH READING MATERIALS OF DESCRIPTIVE TEXT FOR SEVENTH GRADE STUDENT OF SMP AL-WASHLIYAH 8 MEDAN - Yosi Yunita Amalia Siregar; Rafika Dewi Nasution; Juli Rachmadani Hasibuan (Universitas Negeri Medan, 2020)
This study is a Research and Development (R & D) focused on a set of task-based supplementary English reading materials of descriptive texts. The aims of this study is To develop task-based supplementary English reading materials focusing on descriptive texts for Seventh Grade Junior High School Students. The subjects were Grade Seven students of SMP Al-Washliyah 8 Medan Class VII-6. This research used quantitave research. To answer the problems of the study, the data were collected by following the research stages were conducting needs analysis, writing a course grid, designing the first draft, getting expert judgment, and revision. This research was conducted by following Masuhara (in Tomlinson, 1998) research design with several modifications. The result of this research showed that the supplementary reading materials that students need were materials which related to their real life and contain the structure and function of the texts, vocabulary and grammar lesson and interesting reading activities which allow them to interact with the teacher and other students. The product of this study was a set of task-based supplementary English reading materials focusing on descriptive texts for Grade VII students of Junior High School entitled “Reading Practice‟. It consisted of three units. Each unit of the developed materials consisted of 20-25 reading activities. Based on the data from the expert judgement, the mean value of all aspects of the three developed units fell into the range of 3.25 ≤ x ≤ 4. It means that the developed materials were categorized as “Very Good”. Thus, it can be concluded that the task-based supplementary English reading materials have been appropriate for Grade VII students of Junior High School.Keywords: English Reading Materials, Masuhara research design, Teaching Reading